(untitled) (Journal of Forensic Medicine & Toxicology, 2024)
Introduction: Identification of the body remains of an unknown person starts with the identification of the sex and then comes age estimation and further precise identifications. In some instances, like natural calamities, the typically used bones such as the skull and pelvic bones are often recovered in a fragmented or destroyed state, thus interfering with sex determination using them. These special situations demand denser bones like the maxillary sinus and the zygomatic bone to identify sex. This study aims to correlate sexual dimorphism with the maxillary sinus dimensions and the bizygomatic distance. The measurements were done using CT (Computed Tomography) scans of 92 males and 92 females retrieved from PACS (Picture archiving and communication system).